Non-ESL teacher trainee's perception towards the teaching of English as second language / Mohd Amir Izuddin Mohamad Ghazali - Mohamad Ghazali, Mohd Amir Izuddin (Faculty of Education, 2014)
The study was conducted to investigate teacher trainee’s perception towards the teaching of English as second language.lt intends to look at the perception of non-ESL teacher trainee in the Faculty of Education UiTM Shah Alam. A total of 4 students were chosen as participants. A survey research method was used. Among the factors examined areage factors and how cultural background has affected their perception towards English as second language. For various reasons, results indicate that the non-ESL teacher trainee believed that English is very important to learn and it provides a lot of benefits for the future undertaking of their professional and personal development.